The potential for onshore wind repowering to hasten the energy transition in the United States - Andreas Mühlbauer; Yuanbei F. Fan; Daniel J. Sambor; Mark Z. Jacobson (Proceedings of the National Academy of Sciences, 2026)
This study explores whether repowering onshore wind farms will help the United States (US) meet a much larger share of its current electricity demand with wind. Repowering upgrades existing wind farms with new turbines, increasing wind-farm capacity and electricity generation, with less new land requirements than greenfield projects. We analyze the US Wind Turbine Database and project the potential of US wind repowering under different scenarios. Results show that repowering alone could more than double the current US onshore wind nameplate capacity, from 153 GW to ~314 GW, at existing farms. The resulting annual onshore wind electricity generation could increase from 453 TWh in 2024 to ~911 TWh for the same weather year after repowering the fleet. Repowering could allow onshore wind to meet 21%, instead of 10.5%, of 2024 US electricity demand. Repowering is a potential multi-billion-dollar industry in the United States.